Effect of steam explosion‐assisted extraction on phenolic acid profiles and antioxidant properties of wheat bran. (31st March 2016) - Liu, Liya; Zhao, Mengli; Liu, Xingxun; Zhong, Kui; Tong, Litao; Zhou, Xianrong; Zhou, Sumei
Abstract: BACKGROUND: The majority of phenolic acids in wheat bran are bound to the cell walls. Hence, a high proportion of phenolic acids cannot be extracted with conventional extraction methods. This study aimed to investigate the efficiency of steam explosion pre‐treatment in increasing the extractability of phenolic compounds from wheat bran. RESULTS: Bound phenolic acids (BPA) can be released by steam explosion‐assisted extraction. Within the experimental range, soluble free phenolic acids (FPA) and soluble conjugated phenolic acids (CPA) increased gradually with residence time and temperature. After steam explosion at 215 °C for 120 s, the total FPA and CPA reached 6671.8 and 2578.6 µg GAE g −1 bran, respectively, which was about 39‐fold and seven‐fold higher than that of the untreated sample. Ferulic acid, the major individual phenolic acids in bran, increased from 55.7 to 586.3 µg g −1 for FPA, and from 44.9 to 1108.4 µg g −1 for CPA. The antioxidant properties of FPA and CPA extracts were significantly improved after treated. Correlation analysis indicated that the antioxidant capacity was in close relationship with phenolic content in FPA and CPA. CONCLUSION: Steam explosion pre‐treatment could be effectively used to release of BPA and enhance the antioxidant capacity of wheat bran. © 2015 Society of Chemical Industry